SIR LAND: VIEWS AND DISCUSSIONS OF SELECT COMMITTEE AND LEGISLATIVE COUNCIL RELATED TO AGRA TENANCY ACT 1926 - Dr. Anshu Chaudhary (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
In the history of land revenue system under British Rule of India, Sir land was always subject of dispute between government and zamindars. Question of Sir Land made heated discussions among members of Select committee and legislative council of United Province. In this paper I am presenting the views of members of select committee related to provisions of Sir land of Agra tenancy Act 1926. I present the detailed discussions of British Government members and other Indian members of select committee in the process of making Agra tenancy Act 1926. Issue of Sir land became very important because some members of select committee were also zamidars. For petty zamindars Sir land was mean of livelihood but on the other hand for big one it was means of luxury life and status of society. Some of Indian zamidars were in opposition of increment of Sir land but most of zamidars supporting to negate the limitation of acquiring Sir land. British Government members of select committee and legislative council of United Provinces opposed the acquiring Sir beyond the scale especially clause 4(dd) and clause 42 which was proposed by the select committee.